1990
DOI: 10.1021/jo00307a019
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of indole alkaloids. A new strategy for (.+-.)-19-oxoaspidospermidine and (.+-.)-19-oxoaspidofractinine

Abstract: Epoxide 23. Compound 22 (150 mg, 0.55 mmol) was dissolved in dichloromethane (5 mL) and cooled (ice bath). m-Chloroperbenzoic acid (150 mg, 0.65 mmol, 70%) was added and the mixture was left (ice bath) for 12 h and then chromatographed (A1203, CH2C12/EtOAc 1:l) to give 23 [oil, 68 mg, 43%; ala^ + 6 4 O

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 2 publications
2
10
0
Order By: Relevance
“…A single diastereoisomer of 24 was isolated, the relative configuration of which was confirmed by 2D‐NOESY experiments. Based on the 33 % yield over these two steps and the 1:1 selectivity of the similar enamine reduction reported by Gramain et al., we suspect our selectivity to be derived from the instability of the undesired diastereomer. To complete the formal total synthesis, the ethyl ester in 24 was converted to the corresponding methyl ketone by treatment with TMSCH 2 Li, after which TFA‐mediated Boc deprotection afforded 19‐oxoaspidospermidine ( 25 ).…”
Section: Figuresupporting
confidence: 67%
See 2 more Smart Citations
“…A single diastereoisomer of 24 was isolated, the relative configuration of which was confirmed by 2D‐NOESY experiments. Based on the 33 % yield over these two steps and the 1:1 selectivity of the similar enamine reduction reported by Gramain et al., we suspect our selectivity to be derived from the instability of the undesired diastereomer. To complete the formal total synthesis, the ethyl ester in 24 was converted to the corresponding methyl ketone by treatment with TMSCH 2 Li, after which TFA‐mediated Boc deprotection afforded 19‐oxoaspidospermidine ( 25 ).…”
Section: Figuresupporting
confidence: 67%
“…Subsequent treatment of 22 with LiHMDS resulted in clean conversion to tetracycle 23 in 87 % yield. Several groups have previously shown the construction of the D ring from similar tetracyclic frameworks in synthetic strategies toward related indoline alkaloids ,,. Based on these precedents, we chose to first reduce the enamine in 23 , followed by dialkylation with 1,3‐diiodopropane.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The absence of W-coupling to H-21 indicated that oxygenation was likely at C-17. This was further confirmed by comparison of the 13 C NMR data with synthetic racemic 17-oxoaspidofractinine (after correcting for the assignments of the carbon shifts) 34 and 19-oxoaspidofractinine, 35,36 which revealed a close correspondence with the former. Kopsonoline (4) is therefore 17-oxoaspidofractinine, and while the racemic form constitutes one of the intermediate compounds in the synthesis of various aspidofractinine alkaloids, [34][35][36] it is here encountered as an optically active natural product for the first time.…”
mentioning
confidence: 54%
“…2). Although the NMR spectra of these compounds have been published previously (Craveiro et al 1983;Cartier et al 1989;Dufour et al 1990), these data were obtained using lowresolution instruments and hence the chemical : 309.1961: 309. , Ob. : 309.1959 by HRMS and a UV spectrum that was quite similar to those of 1 and 3.…”
Section: Resultsmentioning
confidence: 99%